Care Deficit Predictors Among Community-Dwelling Elderly in a Transnational Migration Area: A Cross-Sectional Analytical Study in a Coastal District of West Java, Indonesia - Theresia Putri Sinaga; Ayesh Mahmood; Muhammad Faiz (HM Publisher, 2026)
This cross-sectional analytical study examined predictors of care deficit among 412 community-dwelling elderly persons aged 60 years and older in a labor-exporting district in West Java, Indonesia, an area characterized by high rates of international labor migration. Care deficit, defined as inadequacy in instrumental and social care activities necessary for maintaining independence and well-being in daily living, was present in 189 respondents (45.9%). Data were collected using structured questionnaires assessing care deficit via an 18-item validated scale, intergenerational solidarity via the six-dimensional Bengtson framework adapted to Indonesian context, and social support using the Medical Outcomes Study Social Support Survey. Family migration status, health insurance coverage, government program participation, chronic disease status, living arrangement, and age were also documented. Bivariate analysis revealed significant associations between care deficit and seven variables: intergenerational solidarity (OR 2.42, 95%CI 1.64–3.58), social support (OR 2.38, 95%CI 1.60–3.53), family migration (OR 2.19, 95%CI 1.48–3.24), chronic disease (OR 1.94, 95%CI 1.28–2.93), living arrangement (OR 1.91, 95%CI 1.27–2.87), health insurance (OR 1.90, 95%CI 1.28–2.83), and government program participation (OR 1.83, 95%CI 1.24–2.71). Multiple logistic regression identified five independent predictors: intergenerational solidarity (AOR 2.04, 95%CI 1.33–3.13), social support (AOR 1.91, 95%CI 1.24–2.94), family migration (AOR 1.87, 95%CI 1.22–2.87), chronic disease (AOR 1.61, 95%CI 1.03–2.52), and health insurance (AOR 1.58, 95%CI 1.02–2.45). The model demonstrated adequate fit (Hosmer-Lemeshow p=0.368), explained 21.4% of variance (Nagelkerke R²=0.214), achieved 69.2% classification accuracy, and yielded an AUC of 0.720. Findings highlight how transnational family structures reshape elderly care systems in resource-limited settings.